SANITASI PEMUKIMAN PADA MASYARAKAT DENGAN RIWAYAT PENYAKIT BERBASIS LINGKUNGAN - Ahyanti, Mei (Jurnal Kesehatan, 2020)
Environmental-based diseases (PBL) are a health problem and occur in almost all geographical regions in the world. Every year, environment-based diseases are always found and reported to spread evenly at every Puskesmas in Bandar Lampung City. Settlement sanitation is an important aspect directly related to health and society. "Waterborne Disease" disease is still high, proving that there are still sanitation problems in settlements. The study aims to determine the relationship of settlement sanitation with environmental-based diseases in the city of Bandar Lampung. The study used a cross-sectional design, the population is all households in Bandar Lampung City. The sample was 384 respondents, taken randomly using multistage sampling. The results found 14,3% of respondents had a physical component of an unhealthy house, 45,3% of respondents had an unhealthy sanitation facility, 40,1% of the occupants of the house behaved in an unhealthy manner. The test results statistically concluded that there was a significant relationship between settlement sanitation and the incidence of environmental-based diseases.